2014
DOI: 10.5812/ijem.16130
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Menarcheal Age: Results From the Cohort of Tehran Lipid and Glucose Study

Abstract: Background:Menarche is considered as a milestone in the women’s reproductive life. Most existing studies on factors influencing menarcheal age had cross-sectional designs and their finding were controversial.Objectives:We aimed to determine some factors affecting the age at menarche in a cohort study with an average of ten-year follow-up; the study was conducted within the framework of Tehran Lipid and Glucose Study (TLGS).Materials and Methods:For the purpose of the present study, we recruited all the females… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 25 publications
(33 reference statements)
0
36
1
1
Order By: Relevance
“…The associations between diet and the onset of menses were evaluated but were not shown to be confounders or mediators, in contrast to some previous evidence . Higher animal protein intakes in mid‐childhood were associated with earlier menarche in two contemporaneous cohorts in Germany, the United Kingdom, Colombia, and Iran, while vegetable protein intakes were positively associated with menarcheal age in the same German cohort . A study from a smaller sample in Boston, Massachusetts reported similar results for (energy‐adjusted) animal and vegetable protein .…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The associations between diet and the onset of menses were evaluated but were not shown to be confounders or mediators, in contrast to some previous evidence . Higher animal protein intakes in mid‐childhood were associated with earlier menarche in two contemporaneous cohorts in Germany, the United Kingdom, Colombia, and Iran, while vegetable protein intakes were positively associated with menarcheal age in the same German cohort . A study from a smaller sample in Boston, Massachusetts reported similar results for (energy‐adjusted) animal and vegetable protein .…”
Section: Discussionmentioning
confidence: 77%
“…Furthermore, they will allow inclusion of the Ethiopian sample (also part of the YL study) where, at round 4, almost no girl had experienced menarche. An additional limitation to the present study is that age at menarche was only reported in years, as in several previous studies, 22,23,41,[48][49][50] and no other information, such as date or month of menarche, was elicited, in contrast to longitudinal cohort studies from the Philippines 18 and Australia. 23 Information about the month and year of the first menstrual period would have allowed for the estimation of menarcheal age in months, which in turn would have enhanced the accuracy of our estimates.…”
Section: Discussionmentioning
confidence: 97%
“…Hence, more attention should be paid to the nutritional status of adolescents before menarche, by which they can be physically prepared to overcome PMS complications. Body reserves, including fats, are helpful to prepare the conditions for a proper and timely experience of the Biological age in young girls (10,12).…”
Section: Discussionmentioning
confidence: 99%
“…This study included both breast development and menarche as outcome measures for puberty development in girls, so that prepubertal girls of young ages could also be included. Several studies (Gavela‐Pérez et al, ; Ramezani Tehrani et al, ; Sloboda et al, ; Zhai et al, ) have shown that overweight and obesity status is positively correlated with early puberty. Davison, Susman, and Birch () conducted a longitudinal study with a sample of 183 white girls, and demonstrated that girls with higher percent body fat at 5 and 7 years were more likely to experience early pubertal development at 9 years.…”
Section: Discussionmentioning
confidence: 99%
“…There have been numerous studies of the relationship between body fat and pubertal development, and whether there is a relationship or interaction between them is still the focus of debate. In girls, there have been numerous longitudinal studies demonstrating an inverse association between obesity and puberty timing, as defined by age of menarche, breast development, and pubic hair development (Gavela‐Pérez, Garcés, Navarro‐Sánchez, López; Villanueva, & Soriano‐Guillén, ; Ramezani Tehrani, Mirmiran, Gholami, Moslehi, & Azizi, ; Sloboda, Hart, Doherty, Pennell, & Hickey, ; Zhai et al, ), while a few studies have not found this association (Ferrández et al, ; Mouritsen et al, ). In boys, there have been fewer studies, and the results have been more ambiguous.…”
Section: Introductionmentioning
confidence: 99%